In Situ Thermal Solvent-Free Synthesis of Zeolitic Imidazolate Frameworks with High Crystallinity and Porosity for Effective Adsorption and Catalytic Applications; Crystal Growth & Design; Vol. 21, iss. 9 - Wang Jichao; Chaemchuen Somboon; Klomkliang N. Nikom; Verpoort F. V. K. Frensis Valter Kornelius (2021, 2021)
Title screen